SELF-COMPASSION, SPIRITUALITAS DAN KUALITAS HIDUP PADA LANSIA - Duma Lumban Tobing; Dhia Wita Nadhifa (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
Elderly individuals often experience a decline in physical function and face various complex physical, psychological, and social challenges, which can impact their quality of life. The quality of life of the elderly in nursing homes requires special attention because it also influences their perspective and self-perception.This study aims to analyze the relationship between self-compassion, spirituality, and the quality of life of the elderly in the "X" social institution in Jakarta. The research used a cross-sectional design with a correlational approach. Sampling was conducted using purposive sampling, involving 111 elderly individuals. The research instruments included the Self-Compassion Short Form (SCSSF), The Daily Spiritual Experience Scale (DSES), and WHOQOL-BREF. Univariate analysis was performed using descriptive statistics, while bivariate analysis was conducted using the spearman test. The results showed that the majority of the elderly participants were female (62 people, or 55.9%), with an average age of 72.12 years. A total of 38 elderly individuals (34.2%) had elementary school education, and the average length of stay in the institution was 4.29 years. Most elderly individuals were also found to suffer from gout (54 people, or 48.6%). The chi-square test revealed a significant relationship between self-compassion and quality of life, with a p-value of 0.001 (p < 0.05) and a correlation coefficient of 0.326, indicating a moderately strong relationship. Additionally, there was a significant relationship between spirituality and quality of life, with a p-value of 0.001 (p < 0.05) and a correlation coefficient of 0.30, also indicating a moderately strong relationship.It is recommended that elderly individuals become more actively involved in religious activities provided by social institutions to strengthen their spiritual well-being.